Analisis Hak-Hak Anak Pasca Perceraian Orangtua Menurut Undang-Undang Nomor 35 Tahun 2014 tentang Perubahan Atas Undang-Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak - Pratama, Gilang Favian; Suryono, Ahmad (Journal of Contemporary Law Studies, 2023)
Divorce cases in Indonesia increased again in 2019, reaching 480,618 cases, especially among Muslims. Since 2015, this number has increased every year. According to the latest data, as of early September 2022 there were 4,500 divorce cases submitted to the Jember Regency Religious Court (PA). Eighty percent of them are divorce applications submitted by wives, and the remaining twenty percent are submitted by husbands. Most of the problems faced by women, the majority of whom file lawsuits, are caused by economic factors. Additionally, the presence of third parties, domestic violence, and disagreements are some other justifications for divorce. Children become victims of divorce that occurs between their parents. Children's rights tend not to be fulfilled if their parents divorce. This research uses a statutory approach and a conceptual approach, with a normative juridical research type. There are several aspects that can be done so that children get their rights as stated in Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection, namely the aspects of Litigation and Non-Litigation. Soo to ensure the fulfillment of child support after divorce, this can be done by having binding regulations regarding the payment of child support, establishing an institution that focuses on paying child support, and involving the father's relatives in providing support.